Profile of system and product certification as quality infrastructure in Indonesia - Isharyadi Febrian (De Gruyter, 2021)
Quality is a universal standard that is expected by consumers of a product or service used. Consumers in general cannot individually assess this quality, with the help of an independent third party it can be done. The certification body is one element in the quality infrastructure that plays a role in providing quality assurance of products and services according to applicable standards. There are various certification bodies in Indonesia both for system and product certification, the kinds additionally range in accordance to the scope of certification. However, it is not yet known generally the condition of the system and product certification in Indonesia. The aim of this study is to conduct profiling and analyse the condition of the system and product certification in Indonesia using a comprehensive tool in order to assess part of the quality of a country's infrastructure. The results showed that there were several elements that were fulfilled, especially in terms of legality and national recognition. However, some elements still need improvement so that the certification body can do its part to ensure the quality of products and services.